The subject is the subject: Why TPACK matters in the era of GenAI - Willermark, Sara (Social sciences & humanities open, 2025)
Generative artificial intelligence (GenAI) has quickly gained a prominent role in discussions within education, especially regarding issues such as plagiarism, assessment, and personalized learning experiences. This position paper advocates for research on how GenAI transforms disciplinary knowledge and redefines subject-specific teaching practices. Through a historical exposé on the role of digital technology in education, this inquiry foregrounds an epistemic perspective that examines how research in technological advances is altering the nature of knowledge and its acquisition. Consequently, the TPACK framework is revisited to highlight the complex interplay of technology, pedagogy, and content in the era of GenAI, sparking critical examination of how it alters the conditions for teachers and teaching. It underscores the importance of studies that explore the meaning of TPACK in the evolving landscape and that enhance the framework with contemporary subject-specific examples rooted in practice.